MORAL REFORM BUREAUCRACY AS PREVENTION OF ILLEGAL PAYMENTS TO INDONESIA CLEAN OF CORRUPTION - Herwin Sulistyowati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Starting the third year of his term, President Joko Widodo launch OPP package (Operation Combating Extortion). The spirit of the eradication of extortion seem so terrible. But until now still many findings in the community, if not more entrenched but membudidaya. Illegal Payments or extortion is charging fees in place that should not be charged or levied. Law enforcement to combat illegal payments related to the abuse of office or authority has stipulated in Article 3 of Law Corruption Law 31 Year 1999 jo Law No. 20 of 2001. Occupation (occupation), which also contained a number of power and authority became the main instrument of the possibility of evil. The law with the problem that arises is how the law works to realize the clean state of the culture korupsi.Metode used is normative and sociological approach that looks at the effectiveness of the operation of the Act with symptoms, behavior, and law enforcement by using the Law of Development Theory that the law of view the overall principles and rules that govern the lives of the people in it, including institutions and legal processes to realize it in reality purpose is to build mental, moral character and state officials (officials) are anti-corrupt. Build law not only limited commitment, but as a means to change attitudes and ways of thinking and behavior bureaucratic apparatus and society together. Because a result like this causes a decrease in the level of public confidence in the law, effect on lazy to work, officials absent from their duties. Law enforcement eradication of extortion there must be effective support and commitment from all stakeholders, communicated effectively, control the decisive, strong integrity officers to combat complaints of extortion by creating a network of central and regional level that seriously responded via online. Moral renewal of man as a supervisor and perpetrator eradication of extortion to create good governance and a prosperous society. Keywords : corruption, extortion, renewal bureaucracy